2013
DOI: 10.1186/1471-244x-13-212
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of lithium in subjects with treatment-resistant depression and suicide risk: a protocol for a randomised, independent, pragmatic, multicentre, parallel-group, superiority clinical trial

Abstract: BackgroundData on therapeutic interventions following deliberate self harm (DSH) in patients with treatment-resistant depression (TRD) are very scant and there is no unanimous consensus on the best pharmacological option for these patients. There is some evidence that lithium treatment might be effective in reducing the risk of completed suicide in adult patients with unipolar affective disorders, however no clear cut results have been found so far. The primary aim of the present study is to assess whether add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Specification a priori of the goals of the study and estimation of the proportion of individuals ineligible for the trial due to the individually application of each exclusion criterion to the target population would assist study design. For example, effectiveness studies could place a larger emphasis on the generalizability of their findings whereas efficacy studies may benefit from relatively stringent eligibility criteria to maximize detection of drug-placebo differences (Blanco, Olfson, Goodwin, et al, 2008; Cipriani et al, 2013; Sani et al, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…Specification a priori of the goals of the study and estimation of the proportion of individuals ineligible for the trial due to the individually application of each exclusion criterion to the target population would assist study design. For example, effectiveness studies could place a larger emphasis on the generalizability of their findings whereas efficacy studies may benefit from relatively stringent eligibility criteria to maximize detection of drug-placebo differences (Blanco, Olfson, Goodwin, et al, 2008; Cipriani et al, 2013; Sani et al, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…The Ethics Committee in Verona (coordinating centre) approved the study on May 6th 2009 (Study code: LAST-RD - FARM77Z3BL5.101-03-2009; Approval number 1675). A detailed description of the study methods has already been published [ 5 ]. Patients with a diagnosis of TRD and history of DSH were randomly allocated to (i) add lithium to usual care or (ii) usual care without lithium.…”
Section: Methodsmentioning
confidence: 99%
“…Acts of DSH and suicide during the 12 months of follow-up constituted the composite primary outcome. A sample size calculation [ 5 ] revealed that 210 patients would have 80% power to show a clinically significant advantage associated with lithium treatment. All phases of the trial were recorded following the CONSORT statement [ 6 , 7 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Now, multisystemic therapy versus psychiatric hospitalization was associated with a reduction of SH attempts in a sample of adolescents. Some research suggests that lithium and clozapine may have specific anti‐suicidal properties (Meltzer et al ., ; Cipriani et al ., ). Other study has reported that selective serotonin reuptake inhibitors may be associated with an increase in suicidal behavior particularly in young people (Barbui et al ., ).…”
Section: Discussionmentioning
confidence: 97%